PERILAKU ALTURISME KARYAWAN (STUDI KASUS PADA MANDOR PERKEBUNAN SAWIT PERSEROAN TERBATAS (PT).TRIBUANA MAS KABUPATEN TAPIN) - Wulandari, Asty (Faculty of Ushuluddin and Humanities, 2017)
One of the tasks of developing into adulthood is to work to meet the needs of his life. Technological advances, materialism, hedonism and the demands of the post-industrial society's needs make some people work brutally for what they want to be fulfilled. Even people are apathetic to the surrounding environment. Nevertheless, there are still a handful of employees who care about their environmental conditions by behaving altruism as happened in PT.Tribuana Mas (TBM). The purpose of this study is to describe employee altruism behavior and explore the factors that encourage employees to behave altruism. The results of the research on 3 employees of PT.Tribuana Mas plantation, Afdeling Juliet conducted qualitatively (nonparticipant observation and in-depth interview), altruism behavioral components are mostly the same, that is behaving helpfully, considering the rights and welfare of others, sharing and honesty. While the different components are seen from the behavior of donating & generosity and Cooperation. Components of altruism behavior reflected on the employees are also in accordance with the teachings of Islam, the namely charity with the foundation of god (ikhlas) and there are still nuanced humanity. It is influenced by various factors, both situational (external) and within (internal)